Effect of In vitro Gastrointestinal Digestion on the Bioaccessibility of Phenolic Compounds and Antioxidant Activity of Manuka Honey. Issue 1 (24th October 2019) - Cianciosi, Danila; Forbes‐Hernández, Tamara Yuliett; Giampieri, Francesca; Zhang, Jiaojiao; Ansary, Johura; Pacetti, Mattia; Quiles, Josè L.; Simal‐Gandara, Jesus; Battino, Maurizio
Abstract : The aim of this study was to investigate and compare the change in the total content of phenolic compounds, flavonoids, and the antioxidant capacity in Manuka Honey (MH) after gastrointestinal digestion and different purification methods. MH was subjected to an in vitro gastrointestinal simulation process, and various spectrophotometric analyses [total phenolic content, total flavonoid content (TFC), 2, 2‐diphenyl‐1‐picrylhydrazyl, ferric ion reducing antioxidant power, and Trolox equivalent antioxidant capacity] were carried out on raw MH and on bioaccessible and eliminated fractions. Our results demonstrated that there was a significant decrease in the quantity of phenolic compounds (between 3.59% and 1.52% of the total amount of phenolic compounds found in undigested honey) and flavonoids in the bioaccessible fraction (between 15% and 19% of the TFC found in undigested honey) after gastrointestinal digestion and that the decrease was lower also for the antioxidant activity of the samples (ranging between 12.39% and 13.67% of the activity of raw honey), suggesting that the phenolic compounds are not only responsible for this activity. Additionally, we demonstrated that the purification method can affect the amount of phenolic compounds and the antioxidant capacity, showing that centrifugation is the most efficient method of purification.